Opportunities promoting social inclusion in elementary school learning context: study of Merdeka Curriculum the Indonesian policies on GEDSI (Gender, Disability, and Social Inclusion) framework - Nurbayanti, Saskia; Iqlima, Zsazsa Ghania; Fauzi, Muhammad Fahmi; Lestari, Triana (Universitas Negeri Yogyakarta, 2024)
Social inclusion is an effort to improve the dignity of disadvantaged individuals so that they can engage in social life. This research explains how the Merdeka Curriculum can direct students as social beings who have character and can accept various roles in the surrounding community. In essence, social inclusion is beginning to take shape and play a crucial role in education. The purpose of this research is to examine the potential of the Merdeka Curriculum policy in promoting social inclusion in the elementary school learning context. Bibliometric analysis is employed to examine publication trends using the Google Scholar database from 2013 to 2023. A total of 760 articles gathered from Publish or Perish are then subjected to data visualization analysis using a VOS viewer to obtain network, overlay, and density visualization. The research findings indicate that studies related to the Merdeka Curriculum significantly increased in 2023 in line with its implementation, but studies addressing social inclusion were relatively scarce. Based on network visualization, 59 terms are grouped into 9 clusters. The term 'Multiculturalism' exhibited a relatively high link strength in connection with terms such as 'new curriculum,' 'modern,' and 'national curriculum' in the current context of the Merdeka Curriculum policy. Other terms found include 'diversity,' 'social inclusion,' and 'social cohesion.' The co-authorship analysis identified 1543 contributing authors. Given Indonesia's multicultural nature, characterized by diversity in various dimensions, Researchers focus the findings of this research as a guide for educators to consistently provide inclusive, comprehensive, and interesting teaching approaches to all students.